Deposit savings and criteria impacting its usefulness - Lela Oniani, Merab Diasamidze, Tamar Ghoghoberidze (Mathematical Statistician and Engineering Applications, 2023)
Savings is one method for achieving a person's financial goals and well-being, i.e., setting away money for future purposes. After monthly household expenses, you should save a small portion of your income and make it a habit; this will help us achieve our goals in the future, and it is essential to keep the savings secure. And now we confront a conundrum: where to keep the savings. Bank or pension fund? Where will it be more efficient and trustworthy to make a "micro" investment with our savings, which can reach a "macro" level in importance in the future?